PENINGKATAN PEMANFAATAN LAHAN DAN MODAL PADA USAHATANI KELAPA DI DESA PANII KECAMATAN DAMSOL KABUPATEN DONGGALA - Effendy Effendy (Universitas Tadulako, 2011)
This research aim was to identify (1) The income level of monoculture and intercropping coconut farms and (2) the relationship of increasing capital and income in farm coconut. The research location was purposively chosen at Panii Village, Damsol Subdistrict of Donggala Regency. Respondents were randomly determined the toss system based on the assumption that the coconut farm condition was homogeny including: (1) land area size, and (2) self own farm. The number of population was 101 households within which 51 household samples were chosen (19 households for monoculture coconut farm and 31 households for intercropping coconut farm). The product moment correlation was used to analyze the relationship of increasing capital and income while descriptive analysis was used to identify the income level. Results of research indicated that (1) the average income of the monoculture and intercropping coconut farms were IDR 2,266,881.53 and IDR 4,859,982.97 ha-1 harvesting-1, respectively, and (2) the correlation of capital and income in coconut farm at Panii village was positive and significant.